Komunikasi Bisnis Dalam Berwirausaha di Era Digital Pada Panti Asuhan Fajar Harapan - Loveana Syaifora; Muhammad Fahrozi; Annesa Adriyani; Hanifahturahmi; Alief Feisal Haznil (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Business communication is communication used in the business world which includes various forms of communication, both verbal and non-verbal to achieve a certain goal. Counseling on business communication in entrepreneurship in the digital era at the Fajar Harapan Pekanbaru Orphanage is an activity that can provide knowledge and understanding about business in entrepreneurship in the digital era and the importance of effective communication. The method of community service activities using socialization and discussion is considered quite appropriate to explore the problems experienced by marketers, so that effective solutions can be obtained. This counseling activity was also welcomed by the local orphanage. This service was carried out at the Fajar Harapan Pekanbaru Orphanage. Based on the results of the community service activities, this counseling went smoothly with good teamwork and the active participation of all participants and it is hoped that it can provide benefits for participants, especially in training good communication skills in entrepreneurship and being able to develop their businesses by utilizing technology and the internet.